Corynespora Cassiicola Leaf Spot of Ceiba pentandra and its Control in the Nursery - Mehrotra, M. D. (Indian Forester, 1989)
A new leaf spot of Ceiba pentandra caused by Corynespora cassiicola is described for the first time from India The disease was highly destructive during the winter months infecting aod damaging about 40 per cent of the leaf area. Infection spots were produced in large number but mostly the spots were below 2-3 mm and big spots, 4-12 mm in size were relatively few in number. The disease bas been successfully controlled by the application of Bavistin at fortnightly interval Dithane M-45 was almost equally effective followed by Blitox and Captaf. On the orber band, Foltaf was not significantly different from control.